Genomic characterization and outbreak investigations of methicillin-resistant Staphylococcus aureus in a county-level hospital in China - Huang, Linyao; Zhu, Liangrong; Yan, Jianxin; Lin, Yajing; Ding, Ding; He, Long; Li, Yexuzi; Ying, Yi; Shen, Lijiong; Jiang, Yuhan; Cai, Haijun; Jiang, Tian (Frontiers in Microbiology, 2024)
Methicillin-resistant Staphylococcus aureus (MRSA) is a common pathogen contributing to healthcare-associated infections, which can result in multiple sites infections. The epidemiological characteristics of MRSA exhibit variability among distinct regions and healthcare facilities. The aim of this study was to investigate the molecular epidemiology and nosocomial outbreak characteristics of MRSA in a county-level hospital in China. A total of 130 non-repetitive MRSA strains were collected from December 2020 to November 2021. Whole-genome sequencing (WGS) was performed to identify antimicrobial resistance and virulence factors. Phylogenetic analysis was conducted to ascertain genetic diversity and phylogenetic relationships. Independent transmission scenarios were determined by the phylogeny derived from single nucleotide polymorphisms (SNPs) within the core genome. All the MRSA isolates were collected from the intensive care unit (30.00%, 39/130), the department of otorhinolaryngology (10.00%, 13/130) and the department of burn unit (9.23%, 12/130). The clinical samples mainly included phlegm (53.85%, 70/130), purulent fluid (24.62%, 32/130), and secretions (8.46%, 11/130). The resistance rates to erythromycin, clindamycin and ciprofloxacin were 75.38, 40.00, and 39.23%, respectively. All the isolates belonged to 11 clonal complexes (CCs), with the major prevalent types were CC5, CC59, and CC398, accounting for 30.00% (39/130), 29.23% (38/130), and 16.92% (22/130), respectively. Twenty sequence types (STs) were identified, and ST59 (25.38%, 33/130) was the dominant lineage, followed by ST5 (23.84%, 31/130) and ST398 (16.92%, 22/130). Three different SCCmec types were investigated, most of isolates were type IV (33.85%, 44/130), followed by type II (27.69%, 36/130) and type III (0.77%, 1/130). The common clonal structures included CC5-ST5-t2460-SCCmec IIa, CC59-ST59-t437-SCCmec IV and CC398-ST398-t034-SCCmec (−), with rates of 16.92% (22/130), 14.62% (19/130), and 13.84% (18/130), respectively. Only 12 panton-valentine leucocidin (PVL) positive strains were identified. Two independent clonal outbreaks were detected, one consisting of 22 PVL-negative strains belongs to CC5-ST5-t2460-SCCmec IIa and the other consisting of 8 PVL-negative strains belongs to CC5-ST5-t311-SCCmec IIa. Overall, our study indicated that the CC5 lineage emerged as the predominant epidemic clone of MRSA, responsible for nosocomial outbreaks and transmission within a county-level hospital in China, highlighting the necessity to strengthen infection control measures for MRSA in such healthcare facilities.